THE CONCEPT OF GENDER AND RELATED THEORETICAL FRAMEWORK - Rizvance Masan, Sehida (International Scientific Journal Vision, 2022)
Considering the fact that society treats women and men differently by assigning different characteristics, roles and responsibilities, the increasing number of studies on the causes of these differences has drawn attention to the concepts of "sex" and "gender". The concept of gender can be named as the stereotypes, judgments and prejudices acquired by the individual regarding gender during the socialization process, unlike the biological sex of the person. Gender is a socio-cultural phenomenon that emerges with the socialization process of the individual. The concept of gender is used to express the qualities built within the complex social relations network, the meanings attributed to femininity and masculinity, and the behaviors expected from them, apart from the concept of gender, which denotes the biological characteristics that define men and women. In this study, sex, gender roles, Gender equality/ Gender inequality and related theoretical approaches will be discussed in order to better understand the concept of gender.